Viral hepatitis morbidity and mortality data in major urban cities in the Philippines - Manriquez, Rael S.; Torres, Mark Anthony J.; Demayo, Cesar G. (International Journal of Public Health Science (IJPHS), 2025)
This study investigates the transmission, impact, and prevention of viral hepatitis A (HAV), hepatitis B (HBV), hepatitis C (HCV), hepatitis D (HDV), and hepatitis E (HEV) in the National Capital Region (NCR) and Region 7, Philippines, from 1960 to 2020. These infections significantly contribute to liver complications, including cirrhosis and hepatocellular carcinoma, affecting mental well-being and posing risks to pregnant women. Although hepatitis mortality is notable, complete treatment can mitigate the risk. Transmission occurs through various routes, such as blood products, body secretions, and perinatal routes. The study underscores the importance of understanding transmission and implementing screening and prevention measures. Vaccination, particularly for Hepatitis A and B, is crucial, reshaping disease epidemiology through universal infant immunization. Challenges like low vaccination coverage persist, especially among children and healthcare workers. Analyzing mortality data reveals a significant recent decrease attributed to government efforts and vaccination programs since 1995. Despite regional variations, mortality remains relatively low. The study recommends prioritizing and expanding vaccination programs, raising awareness, improving healthcare accessibility, and strengthening surveillance systems. Coupled with community engagement, these measures promise sustained success against viral hepatitis, reinforcing the observed trend in mortality reduction.